Estrategias de marketing y su incidencia en el posicionamiento de la empresa calzacuba, en el cantón Latacunga, periodo 2014-2015 - Estrella Rodríguez, Sandra Jeaneth (2015)
For making the present investigation the next main objective was planted; designing marketing strategies for Calzacuba Company which ones let increasing its positioning inside the national market, therefore situational analyses was made an research inside the enterprise looking for current institutional situation where it is developing, internal and external activities through a F.O.D.A. analyses determining as principal problem the lack market placing about low applied strategies on its offered products. The methodology used was inductive, deductive and statistical methods that produced some data by interviews, questionnaires, quizzes and observation records, due company necessities were found as marketing strategies application for its placing....